Identifying Acute Cardiac Hazard in Early Drug Discovery Using a Calcium Transient High-Throughput Assay in Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Lu, Hua Rong; Kreir, Mohamed; Karel, Van Ammel; Tekle, Fetene; Geyskens, Danny; Teisman, Ard; Gallacher, David J. (Frontiers in Physiology, 2022)
Identifying Acute Cardiac Hazard in Early Drug Discovery using a Calcium Transient High-Throughput assay in Human Induced Pluripotent Stem Cell-derived Cardiomyocytes (hiPSC-CMs)